A Theoretical and Empirical Analysis of the Roles of Instructional Leadership, Teacher Collaboration, and Collective Efficacy Beliefs in Support of Student Learning - Goddard, Roger; Goddard, Yvonne; Kim, Eun Sook; Miller, Robert (American Journal of Education, 2015)
Principals' instructional leadership may support the degree to which teachers work together to improve instruction, and together leadership and teacher collaboration may contribute to school effectiveness by strengthening collective efficacy beliefs. We found a significant direct effect of leadership on teacher collaboration. Further, leadership and collaboration predicted collective efficacy beliefs. Finally, achievement differences among schools were predicted directly by collective efficacy beliefs and indirectly by instructional leadership and teacher collaboration. These findings suggest that strong instructional leadership can create structures to facilitate teachers' work in ways that strengthen organizational belief systems, and, in concert, these factors foster student learning.
Keywords: Academic Achievement; Beliefs; Instructional Leadership; Predictor Variables; Principals; School Effectiveness; School Involvement; Self Efficacy; Structural Equation Models; Teacher Attitudes; Teacher Collaboration